A deletion mutation in TaHRC confers Fhb1 resistance to Fusarium head blight in wheat - Su, Zhenqi; Bernardo, Amy; Tian, Bin; Chen, Hui; Wang, Shan; Ma, Hongxiang; Cai, Shibin; Liu, Dongtao; Zhang, Dadong; Li, Tao; Trick, Harold; St. Amand, Paul; et al. (Nature genetics, 2019)
Fusarium head blight (FHB), which is mainly caused by Fusarium graminearum , is a destructive wheat disease that threatens global wheat production. Fhb1 , a quantitative trait locus discovered in Chinese germplasm, provides the most stable and the largest effect on FHB resistance in wheat. Here we show that TaHRC , a gene that encodes a putative histidine-rich calcium-binding protein, is the key determinant of Fhb1 -mediated resistance to FHB. We demonstrate that TaHRC encodes a nuclear protein conferring FHB susceptibility and that a deletion spanning the start codon of this gene results in FHB resistance. Identical sequences of the TaHRC-R allele in diverse accessions indicate that Fhb1 had a single origin, and phylogenetic and haplotype analyses suggest that the TaHRC-R allele most likely originated from a line carrying the Dahongpao haplotype. This discovery opens a new avenue to improve FHB resistance in wheat, and possibly in other cereal crops, by manipulating TaHRC sequence through bioengineering approaches. Genetic studies using map-based cloning, gene editing, RNA interference, haplotyping and association analyses identify a deletion in TaHRC as a key determinant of Fhb1 -mediated resistance to Fusarium head blight in wheat.